Análisis comparativo del rendimiento del tráfico en redes MPLS con túneles ipsec en entornos IPv6. - Romero Chafla, Juan Sebastian (2016)
Every day the information from the IP networks requires process and methods that permit resolve security issues on specific networks environments, there are a lot of specifications and applications that works in different implementations on layer 3, but the networks administrators must provide and implement security protocols for solving problems such as updating obsolete protocols, implementing new technologies like MPLS, routing protocols like IPv6 and the networks needs to increase levels of the critical information that cross the networks environments, that´s because a security protocols must be implemented with IPSec tunnels and verify the network environment performance including new generation protocols (IPv6) over MPLS network. At first the actual physical and logical topology of the local network of the Universidad Politécnica Salesiana will be analyzed to propose the future security protocols and make recommendations to upgrade the technologies on each campus. A comparative analysis will be made between two sceneries, one of them implementing without IPSec and the other one with IPSec with an encryption algorithms like ISAKMP, IPSec Tunnel, key sharing method, over MPLS environment and including IPv6 routing in each campus, in order to demonstrate a possible implementation. Finally, the simulation will be with the software GNS3, using a physical and logical design with the security and routing protocols, capturing packets on the network making a comparative analysis, obtaining in this way important information like transmission speed, number of packets and average percentage about the network performance in order to demonstrate that a future security protocol could be implement.